A STUDY ON INVESTOR BEHAVIOUR ON FUNDAMENTAL ANALYSIS - Trivedi, Yagnesh; Raval, Dharmesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The passage discusses the historical roots and contemporary applications of analysis in various fields, particularly in the context of financial decision-making. It emphasizes the behavioural biases of financial professionals and explores how fundamental analysis and technical analysis are employed in corporate financial management. The text further delves into the basics of accounting and financial analysis, highlighting two approaches: bottom-up and top-down analysis. It introduces technical analysis as a method to predict price fluctuations in financial markets based on historical charts and market statistics. The importance of fundamental analysis in assessing the intrinsic value of securities is also underscored, requiring a deep understanding of economic factors. Overall, the passage provides a comprehensive overview of analysis methods in finance.